Taking sides : - Noll, James W. (James William) (McGraw-Hill / Irwin, 2006)
This debate-style reader is designed to introduce students to controversies in global issues through readings that reflect a variety of viewpoints. Each issue is framed with an issue summary, an issue introduction, and a postscript. The Taking Sides readers feature annotated listings of selected World Wide Web sites. Taking Sides is supported by our student website at www.dushkin.com/online